2013
DOI: 10.1017/s1461145713000497
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability is a trait marker of major depressive disorder: evidence from the sertraline vs. electric current therapy to treat depression clinical study

Abstract: Decreased heart rate variability (HRV) is a cardiovascular predictor of mortality. Recent debate has focused on whether reductions in HRV in major depressive disorder (MDD) are a consequence of the disorder or a consequence of pharmacotherapy. Here we report on the impact of transcranial direct current stimulation (tDCS), a non-pharmacological intervention, vs. sertraline to further investigate this issue. The employed design was a double-blind, randomized, factorial, placebo-controlled trial. One hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 64 publications
7
114
0
Order By: Relevance
“…Thus neuropathological changes in the mPFC may result in the reduction in parasympatheticto-sympathetic tone observed in a proportion of mood disorder patients, potentially explaining the elevated risk for ventricular tachycardia and myocardial infarction in depressed patients with cardiovascular disease (Carney et al, 2005). The reduction in parasympathetic and vagal tone observed in depressed and manic subjects (Brunoni et al, 2013;Henry et al, 2010;Kemp et al, 2012;Udupa et al, 2007) may additionally result in abnormal autonomic responses, and by implication abnormal affective responses to both internal or external stimuli. For instance, Lane et al (2009) reported that the vagally-mediated component of heart rate variability correlated with changes in regional cerebral blood flow (rCBF) in the mPFC during the induction of happiness, sadness, and disgust.…”
Section: Discussionmentioning
confidence: 99%
“…Thus neuropathological changes in the mPFC may result in the reduction in parasympatheticto-sympathetic tone observed in a proportion of mood disorder patients, potentially explaining the elevated risk for ventricular tachycardia and myocardial infarction in depressed patients with cardiovascular disease (Carney et al, 2005). The reduction in parasympathetic and vagal tone observed in depressed and manic subjects (Brunoni et al, 2013;Henry et al, 2010;Kemp et al, 2012;Udupa et al, 2007) may additionally result in abnormal autonomic responses, and by implication abnormal affective responses to both internal or external stimuli. For instance, Lane et al (2009) reported that the vagally-mediated component of heart rate variability correlated with changes in regional cerebral blood flow (rCBF) in the mPFC during the induction of happiness, sadness, and disgust.…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors that influence on depression have been associated with the decreased cardiac vagal control. It may be a trait marker for MDD [17] which can be used for evaluating and classifying the severity of symptoms in these patients. This study aimed to compare heart rate variability between patients with the major depressive disorder and normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we found that the blood levels of several cytokines (IL-2, IL-4, IL-6, IL-10, IL-17a, IFN-γ) decreased after tDCS treatment, but also in the placebo arm (Brunoni et al, 2014c) and that heart rate variability did not change after tDCS treatment, regardless of treatment response (Brunoni et al, 2013a),. Thus, neither the HPA axis nor the autonomous nervous system are majorly implied in the antidepressant mechanisms of tDCS, at least during the MDD acute phase.…”
Section: Discussionmentioning
confidence: 81%